If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(2x-7)+6x=-19
We move all terms to the left:
-5(2x-7)+6x-(-19)=0
We add all the numbers together, and all the variables
6x-5(2x-7)+19=0
We multiply parentheses
6x-10x+35+19=0
We add all the numbers together, and all the variables
-4x+54=0
We move all terms containing x to the left, all other terms to the right
-4x=-54
x=-54/-4
x=13+1/2
| (-14)x(Z)=24 | | -4(2n-3)=12.8n | | 12x+9-4x-4=3x-x+30 | | -9(s+23)=9 | | 57=3(c-72) | | -98=-9r+-17 | | 4x=9/(3x+5) | | 45=3(c-58) | | 6(h-81)=12 | | 9=15+2t | | 8(u-86)=16 | | 2=c/4-3 | | 9/10x-2/5=2 | | -2-34=x | | 12=r/2+8 | | 0.2(d+5)=42 | | 1/5(d+5)=42 | | 32=(-2)-5z | | 32=-2-5z | | Y=$1.75x-$15 | | 10a-27=12a+41 | | 20(d+5)=42 | | -2-5z=32 | | 0.666x-2+0.166=0.416 | | (-14)z-18=6 | | 14x=42+86 | | 5(3/4)x=-1 | | 18-(16(z))=(-4) | | 10m+4=m+22 | | 16(z)=14 | | -5x+3x=7x-5x+2 | | 44=6x |